1993
DOI: 10.1111/j.1600-0404.1993.tb05359.x
|View full text |Cite
|
Sign up to set email alerts
|

Ataxia and areflexia in SOAA

Abstract: Fifteen patients with the classical syndrome of ophthalmoplegia, ataxia, and tendon areflexia (SOAA) were studied in an attempt to clarify the mechanisms of ataxia and myotatic hyporeflexia. All showed features of cerebellar rather than sensory ataxia. Peripheral nerve conduction studies, including F-waves, were normal in a majority of the patients, as was needle EMG. Low-amplitude compound sensory nerve potentials were seen in four patients only, and mild slowing of sensory conduction velocity in two. Three h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Some investigators have suggested that lesions scattered in the brainstem tegmentum and cerebellar peduncles are responsible for ataxia and areflexia [24], but neurophysiological study results suggest that peripheral abnormalities occur in some FS patients [11,14,31]. Similar findings in previous reports include reduced amplitudes of sensory nerve action potentials and the absence of soleus H-reflexes in some FS patients, * Absent H-reflexes defined as abnormal ** Power spectrum peak at 1-Hz regarded as abnormal Table 5 Nerve conduction study, somatosensory evoked potential, and postural body sway analyses in patients with Bickerstaff's brainstem encephalitis (BBE) and Fisher syndrome (FS) but the number of those examined was too small to reach a definite conclusion.…”
Section: ■ Both Cns and Pns Involvementmentioning
confidence: 99%
“…Some investigators have suggested that lesions scattered in the brainstem tegmentum and cerebellar peduncles are responsible for ataxia and areflexia [24], but neurophysiological study results suggest that peripheral abnormalities occur in some FS patients [11,14,31]. Similar findings in previous reports include reduced amplitudes of sensory nerve action potentials and the absence of soleus H-reflexes in some FS patients, * Absent H-reflexes defined as abnormal ** Power spectrum peak at 1-Hz regarded as abnormal Table 5 Nerve conduction study, somatosensory evoked potential, and postural body sway analyses in patients with Bickerstaff's brainstem encephalitis (BBE) and Fisher syndrome (FS) but the number of those examined was too small to reach a definite conclusion.…”
Section: ■ Both Cns and Pns Involvementmentioning
confidence: 99%